2020
DOI: 10.1111/ced.14388
|View full text |Cite
|
Sign up to set email alerts
|

Lymecycline vs. clindamycin plus rifampicin in hidradenitis suppurativa treatment: clinical and ultrasonography evaluation

Abstract: Background. Antibiotic therapy remains the first-line treatment for hidradenitis suppurativa (HS). However, literature data on its comparative clinical efficacy and safety are limited. Aim. To investigate the efficacy of tetracycline (lymecycline 300 mg daily) vs. the combination therapy clindamycin and rifampicin (600 mg plus 600 mg daily) by evaluating and comparing the clinical response at the end of antibiotic treatment (10 weeks). Methods. The study retrospectively analysed 52 patients divided in two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
(91 reference statements)
1
15
1
1
Order By: Relevance
“…HRQoL, assessed by the DLQI, improved more in patients treated with clindamycin than in the patients treated with clindamycin plus rifampicin [ 58 ]. ‘More marked’ HRQoL improvement, as measured by the DLQI, occurred in patients treated with tetracycline alone compared to patients treated with a combination of clindamycin and rifampicin [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…HRQoL, assessed by the DLQI, improved more in patients treated with clindamycin than in the patients treated with clindamycin plus rifampicin [ 58 ]. ‘More marked’ HRQoL improvement, as measured by the DLQI, occurred in patients treated with tetracycline alone compared to patients treated with a combination of clindamycin and rifampicin [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the Hurley clinical grading system is commonly used for screening and grading severity of HS, 2 the IHS4 – recognized as simple to use and adapted for clinical research and daily practice 6 – has been validated and reported in several clinical studies for assessing HS response 8,17,20‐23 . To our knowledge, SOLACE is the first study reporting changes in IHS4 scores observed by baseline AN count.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is known from literature that fistulas are poorly responsive to the currently available medical treatments. 6,[9][10][11][12][13][14] At the same time,…”
Section: Discussionmentioning
confidence: 96%
“…1 It is known from literature that fistulas are poorly responsive to the currently available medical treatments. 6,[9][10][11][12][13][14] At the same time, these lesions play a central role in the "window of opportunity" acting as a sort of watershed between medical and surgical approach. 6 Therefore, the analysis of their features related to their clinicalsonographic response may indicate when the medical therapy alone might be still effective.…”
Section: Discussionmentioning
confidence: 99%